The Relationship Between the Leadership of Wirid Yasin Administrators and Members’ Participation in Attending the Monthly Wirid in Jorong Seroja, Tanah Datar Regency - Vatika Rahmadani, Chyndy; Ismaniar, Ismaniar (Universitas Negeri Padang, 2026)
level of member participation in attending Yasin recitation activities in Jorong Seroja, Tanah Datar Regency. This situation is believed to be associated with the leadership practices of the Yasin recitation management, which have not been implemented optimally. Therefore, leadership of the Yasin recitation management and member participation in attending the monthly Yasin recitation activities in Jorong Seroja, Tanah Datar Regency. The research employed a correlational research design. The population of the study consisted of 60 active members. a questionnaire and subsequently analyzed using percentage formulas and the product moment correlation technique. The results of the study indicate that: (1) the leadership of the Yasin recitation management is categorized as poor, (2) the level of member participation is also categorized as poor leadership of the Yasin recitation management and member participation in attending the monthly Yasin recitation activities in Jorong Seroja, Tanah Datar Regency. apply leadership practices in a more regular and consistent manner to improve member participation.